2015
DOI: 10.1042/cs20140705
|View full text |Cite
|
Sign up to set email alerts
|

Novel MTND1 mutations cause isolated exercise intolerance, complex I deficiency and increased assembly factor expression

Abstract: Complex I (CI) is the largest of the five multi-subunit complexes constituting the human oxidative phosphorylation (OXPHOS) system. Seven of its catalytic core subunits are encoded by mitochondrial DNA (ND (NADH dehydrogenase)1–6, ND4L (NADH dehydrogenase subunit 4L)), with mutations in all seven having been reported in association with isolated CI deficiency. We investigated two unrelated adult patients presenting with marked exercise intolerance, persistent lactic acidaemia and severe muscle-restricted isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…We have shown that specific genotypes present similar patterns of mitochondrial deficiency, consistent with the known biochemical defect. For example, patients harbouring compound heterozygous LRPPRC mutations showed isolated COX deficiency 44 45 46 , whilst the patient carrying the m.4175G > A MT-ND1 mutation showed isolated complex I deficiency 47 48 49 50 .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that specific genotypes present similar patterns of mitochondrial deficiency, consistent with the known biochemical defect. For example, patients harbouring compound heterozygous LRPPRC mutations showed isolated COX deficiency 44 45 46 , whilst the patient carrying the m.4175G > A MT-ND1 mutation showed isolated complex I deficiency 47 48 49 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Isolated mitochondrial myopathies have characteristically presented as sporadic cases due to heteroplasmic mutations in protein-coding genes of mtDNA [14,15] in mt-tRNA genes [5][6][7][8], and recently also with mutations in nuclear genes causing autosomal recessive disorders such as ISCU and FDX1L [16,17]. In the era of next-generation sequencing, it is important to realize that many mtDNA mutations are somatic and can only be detected in DNA isolated from muscle [14,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a 4175G>A mutation in human MTND1 , a homolog of plant NAD1 , has been identified that causes defective complex I assembly. 60 It converts the codon from being translated as Trp to a stop codon, which halts translation and may cause complex I disassembly. These authors have suggested that the conserved Trp residue plays an important role in human mitochondrial complex I functionality.…”
Section: Discussionmentioning
confidence: 99%